Part-time cancers and role of melatonin in determining their metabolic phenotype - Reiter, Russel J.; Sharma, Ramaswamy; Rodriguez, Carmen; Martin, Vanesa; Rosales-Corral, Sergio; Zuccari, Debora Aparecida Pires de Campos; Chuffa, Luiz Gustavo de Almeida (Elsevier, 2021)
This brief review describes the association of the endogenous pineal melatonin rhythm with the metabolic flux of solid tumors, particularly breast cancer. It also summarizes new information on the potential mechanisms by which endogenously-produced or exogenously-administered melatonin impacts the metabolic phenotype of cancer cells. The evidence indicates that solid tumors may redirect their metabolic phenotype from the pathological Warburg-type metabolism during the day to the healthier mitochondrial oxidative phosphorylation on a nightly basis. Thus, they function as cancer cells only during the day and as healthier cells at night, that is, they are only part-time cancerous. This switch to oxidative phosphorylation at night causes cancer cells to exhibit a reduced tumor phenotype and less likely to rapidly proliferate or to become invasive or metastatic. Also discussed is the likelihood that some solid tumors are especially aggressive during the day and much less so at night due to the nocturnal rise in melatonin which determines their metabolic state. We further propose that when melatonin is used/tested in clinical trials, a specific treatment paradigm be used that is consistent with the temporal metabolic changes in tumor metabolism. Finally, it seems likely that the concurrent use of melatonin in combination with conventional chemotherapies also would improve cancer treatment outcomes.
Keywords: Hypoxia inducible factor; Mitochondria; Oxidative phosphorylation; Pyruvate dehydrogenase; Pyruvate dehydrogenase kinase; Warburg metabolism